Androgenic Control of TGF-β Signaling in Prostate Epithelial Cells through Transcriptional Suppression of TGF-β Receptor II - Song, Kyung (2008)
The androgen receptor crosstalks with transforming growth factor-β (TGF-β) through mechanisms that remain poorly understood. Here we provide strong evidence that 5α-dihydrotestosterone (DHT) intercepts the ability of prostate epithelial cells to undergo TGF-β-induced apoptosis, and present a new model for this androgenic effect. We report that DHT decreases the level of TGF-β receptor II (TβRII) through a transcriptional mechanism, leading to suppression of the ability of TGF-β to down-regulate expression of Bcl-xL and Cyclin Ds, activate caspase-3 and induce apoptosis. Promoter analysis, DNA pulldown and electrophoretic mobility shift assays support that transcriptional downregulation of TβRII by DHT occurs through Sp1/3 response elements, with the binding of Sp1 to the TβRII promoter being suppressed by DHT, largely driven by loss of Sp1 protein and/or activity. These results provide fresh insight on the mechanism of growth control by androgens and progression of prostate cancer to androgen independence.